Interaksi Aktor dalam Pengelolaan Objek Wisata Cekingan di Kabupaten Gianyar - Oka Amiyura, A.A. Meydita; Bandiyah, Bandiyah; Noak, Piers Andreas (Jurnal Nawala Politika, 2021)
This study aims to answer a problem formulation the interaction of actors in managing the tourist attraction of Cekingan. First, the interaction between BPOWC and farmers. The second is BPOWC's interaction with restaurant and art shop entrepreneurs in Cekingan Tourism Object. Third, BPOWC with the Ludden House Community. This research uses Marxism Political Economy Theory and collaborative governance theory. The research method is a descriptive qualitative method. The results of this research are First; conflicts regarding compensation distribution and. Second; especially for residents outside Tegallalang Village by collecting payments. Third; the Ludden House Community is chaired by Gede Suanda, namely the removal of the Bali Not For Sale board by the manager and Bendesa Pakraman. The findings indicate that the management of the two classes is divided. The results of the application of collaborative governance have not involved stakeholders from Kedisan Village in management Keywords: Interaction Actor, Management, Cekingan Tourism.